IBADAH DALAM PERSPEKTIF AL-ISLAM KEMUHAMMADIYAHAN: KAJIAN KONSEPTUAL DAN IMPLEMENTATIF - Qhanita Wulandari Arif; Waode Helvi Mei Hamka; Muhammad Haliq As`sam; Amin Umar (STKIP Subang, 2025)
Worship constitutes the core of Islamic teachings and represents the primary purpose of human creation. This article aims to examine the concept of worship from the perspective of Al-Islam and Muhammadiyah, encompassing its definition, essence, and objectives, the types of worship, legal foundations, principles of worship, and its implementation in human life. The method employed is a library research approach, which analyzes the Qur’an, Hadith, and various relevant scientific journal articles. The findings indicate that worship is not limited to formal ritual practices (hablum minallah), but also includes social dimensions (hablum minannas). Proper implementation of worship is capable of shaping Muslims into individuals who are pious, possess noble character, and demonstrate social responsibility.